2014
DOI: 10.1152/ajpregu.00185.2014
|View full text |Cite
|
Sign up to set email alerts
|

The physiology underlying Roux-en-Y gastric bypass: a status report

Abstract: Lutz TA, Bueter M. The physiology underlying Roux-en-Y gastric bypass: a status report. Am J Physiol Regul Integr Comp Physiol 307: R1275-R1291, 2014. First published September 24, 2014 doi:10.1152/ajpregu.00185.2014.-Obesity and its related comorbidities can be detrimental for the affected individual and challenge public health systems worldwide. Currently, the only available treatment options leading to clinically significant and maintained body weight loss and reduction in obesity-related morbidity and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 164 publications
(334 reference statements)
2
76
0
3
Order By: Relevance
“…Studies using genetic animal models have indicated that neither factor alone is crucial for the metabolic benefits Wilson-Perez et al 2013). Recent, preclinical reports imply that coordinated alteration in multiple systems including bile homeostasis, microbiota, and gut-brain communication functions in concert with humoral alterations to mediate the metabolic effects of surgery (Berthoud et al 2011;Furet et al 2010;Lutz and Bueter 2014;Ryan et al 2014). Identification of these mechanisms could lead to the development of a pharmacological strategy that may reproduce the glycemic control of surgery and render such invasive surgical procedures obsolete.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Studies using genetic animal models have indicated that neither factor alone is crucial for the metabolic benefits Wilson-Perez et al 2013). Recent, preclinical reports imply that coordinated alteration in multiple systems including bile homeostasis, microbiota, and gut-brain communication functions in concert with humoral alterations to mediate the metabolic effects of surgery (Berthoud et al 2011;Furet et al 2010;Lutz and Bueter 2014;Ryan et al 2014). Identification of these mechanisms could lead to the development of a pharmacological strategy that may reproduce the glycemic control of surgery and render such invasive surgical procedures obsolete.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…These post-operative changes are likely to impact energy expenditure, food intake, satiety, glucose, and lipid homeostasis in a weight-loss independent manner [16]. We predict in this exploratory study that performance of a SG has weight-loss independent effects on cardiac dysfunction induced by diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The explanations for its efficacy likely include complex interactions between the peripheral and central nervous system (Berthoud, Shin et al 2011; Lutz and Bueter 2014). Proposed mechanisms for weight loss include increased energy expenditure, enhanced satiety signals, and changes in the preference for certain foods.…”
Section: Introductionmentioning
confidence: 99%
“…It receives neural and hormonal satiety signals from the gut (Dockray 2009; de Lartigue, de La Serre et al 2011), projects to brainstem structures involved in regulating metabolism, e.g. (Zechner, Mirshahi et al 2013; Lutz and Bueter 2014), and has reciprocal connections with forebrain structures involved in food regulation and preference (Rinaman 2010; Rinaman 2011). Moreover, it shows demonstrable plasticity in response to short-term changes in energy balance (Rinaman, Baker et al 1998) as well as changes associated with diet (Covasa, Grahn et al 2000).…”
Section: Introductionmentioning
confidence: 99%